2022
DOI: 10.1038/s41467-022-30319-2
|View full text |Cite
|
Sign up to set email alerts
|

Constructing chemical stable 4-carboxyl-quinoline linked covalent organic frameworks via Doebner reaction for nanofiltration

Abstract: Covalent linkages are the key component of covalent organic frameworks (COFs). The development of stable and functional linkages is essential to expand the COFs family and broaden their application prospects. In this work, we report the synthesis of crystalline and chemical stable 4-carboxyl-quinoline linked COFs (QL-COFs) via Doebner reactions in both one-pot (OP) and post-synthetic modification (PSM) methods. Both methods can be universally applied to most of the reported imine COFs family via bottom-up cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Hence, the electrostatic repulsion between the negatively charged COF membrane surface and anionic MB dye (Donnan effect) also plays a contributory role in the dye rejection performance of the TUS-46 membrane. A water permeance as high as 57.8 LMH bar –1 was achieved (Figure f), which surpasses the water permeances for MB separation by most COF (LZU1: 48.5 LMH bar –1 ; QL-COF2: 43.9 LMH bar –1 ) , and MOF (ZIF-8/PSS: 26.5 LMH bar –1 ; ZIF-11/PAN: 46.4 LMH bar –1 ; ZIF-12/PAN: 27.2 LMH bar –1 ) , membranes with dye rejection rate >95% yet reported. In this contribution, we address the intrinsic hydrophilicity of TUS-46 membranes through direct reticular construction, unlike many other previous reports.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, the electrostatic repulsion between the negatively charged COF membrane surface and anionic MB dye (Donnan effect) also plays a contributory role in the dye rejection performance of the TUS-46 membrane. A water permeance as high as 57.8 LMH bar –1 was achieved (Figure f), which surpasses the water permeances for MB separation by most COF (LZU1: 48.5 LMH bar –1 ; QL-COF2: 43.9 LMH bar –1 ) , and MOF (ZIF-8/PSS: 26.5 LMH bar –1 ; ZIF-11/PAN: 46.4 LMH bar –1 ; ZIF-12/PAN: 27.2 LMH bar –1 ) , membranes with dye rejection rate >95% yet reported. In this contribution, we address the intrinsic hydrophilicity of TUS-46 membranes through direct reticular construction, unlike many other previous reports.…”
Section: Resultsmentioning
confidence: 91%
“…However, an appreciably lower water permeance of 5.2 LMH bar –1 (Figure f) was obtained owing to the hydrophobic character of TAPP-ETTB COF (Figure d). A comparative analysis of the MB rejection performance of the TUS-46 and TAPP-ETTB COF membranes against current state-of-the art membranes is provided in Figure h. ,, , The XRD investigation after dye removal tests validated the retention of the crystallinity of TUS-46 membranes (Figure S18), with no changes in the crystal structure or morphology detected by SEM (Figure S7b). Besides, the long-term hydrolytic stability of TUS-46 could be substantiated from the preservation of crystallinity and chemical makeup after immersing in water over 4 weeks, as evident from the XRD profiles (Figure S13) and FT-IR spectra (Figure S14), respectively.…”
Section: Resultsmentioning
confidence: 91%
“…To achieve the aromatization of the quinoline ring, catalytic amounts of DDQ are required in this reaction . However, aromatization can also be achieved by using acetic acid and O 2 in the COF synthesis as reported recently. , Several reactions were performed to study the influence of different amounts of DDQ. It was found that increasing its concentration has no further effect on aromatization.…”
Section: Resultsmentioning
confidence: 99%
“…Post-synthetic modification (PSM) has been illustrated to be an efficient strategy for locking reversible linkages into stable covalent bonds in COFs; however, PSM requires multi-step reaction and purification processes. To circumvent this, MCRs have been recently discovered as a suitable tool to form robust connectivity within COFs and simultaneously conserving their framework crystallinity. , …”
Section: Introductionmentioning
confidence: 99%
“…24,25 For instance, C = N bonds in imine-linked COFs could be transformed to more robust amide linkages under an oxidizing condition with high conversion e ciency and crystallinity. [26][27][28][29] Similarly, locking of the imine linkage by other organic reactions could afford stable benzothiazole, 30,31 quinoline linkage, [32][33][34][35] , benzoxazole, 36 C-N bond. 37,38 Following these pioneering works, we recently reported a novel oxidant-free PSM method to construct ultrastable nonsubstituted quinoline-linked COFs (labelled as NQ-COFs) via rhodium-catalyzed [4 + 2] annulation.…”
Section: Introductionmentioning
confidence: 99%